The Pulse of Drug Development for Alzheimer's Disease - Rafii, Michael S. (Reviews on Recent Clinical Trials, 2010)
Therapies that are believed to target the underlying mechanisms of Alzheimer's disease have now reached human clinical trials, with the number of agents in late stage development having increased dramatically in recent years. Primary targets include beta-amyloid, whose presence and accumulation in the brain is thought to contribute to the development of Alzheimer's disease, and tau protein which, when hyperphosphorylated, results in the formation of neurofibrillary tangles of paired helical filaments, also believed to be involved in the pathogenesis of Alzheimer's disease. In the review, the current status of Alzheimer's Disease therapies under study is discussed, including the scientific basis for each strategy.
Keywords: Alzheimer' s disease